Importance of Platelet Count and Hematocrit in Dengue Fever in Children (Bangladesh Journal of Child Health, 2021)
Background: Dengue fever has become one of the most important public health concerns now a day due to increasing complications and fatal outcomes. Dengue hemorrhagic fever and dengue shock syndrome are life threatening but reversible complications of dengue fever.Objectives: This study was performed to evaluate the relationship between platelet count and hematocrit with the severity of dengue infection in pediatric age group.Materials & Methods: This was a prospective observational study which included 280 dengue seropositive children of 1 month to 15 years, conducted during 1st June to 30th November, 2018 in a tertiary care hospital of Dhaka.Results: Out of 280 dengue cases, 187(66.78%) had thrombocytopenia and 88(47%) had raised hematocrit. Among the thrombocytopenic patients 44% had dengue fever, 47% had dengue hemorrhagic fever and 9% dengue shock syndrome. A significant co-relation was observed between the severities of thrombocytopenia and raised hematocrit with the appearance of dengue warning signs in case of dengue hemorrhagic fever.Conclusion: Thrombocytopenia and raised hematocrit were related to the severity of dengue hemorrhagic fever.Bangladesh J Child Health 2020; VOL 44 (2) :74-77